Citizenship Education As a Step to Creating the Nation’s Next Generation With Good Character - Fadilah, Nurul (International Journal of Students Education, 2024)
The development of the times has push Lots change to generation successor nation. One of the significant changes is education character child. Without realized education it seems disconnected from real world situations. This research aiming for help student learn rights and obligations they as citizens. The research method used is a literature review. The results of the study show existence significant relationship between education citizenship with create good character to generation successor nation. Therefore that, education citizenship can prepare participant educate become excellent citizen with develop intelligence intellectual, emotional, social, and spiritual. This article also examines spelling errors that are often found in the news education latest,as method for show importance accuracy in writing teaching materials and learning resources. By analyzing previous research, the this article provides insight into the effectiveness of each approach and how its implementation can improve quality learning Civics and involvement student.